Capillary Gas Chromatographic Separation Performances of a Tetraphenyl Porphyrin Stationary Phase - Yan, Yuan; Wang, Zhenzhong; Zhang, Zitong; He, Zhen; Luo, Lun; Fan, Jing (Frontiers in Chemistry, 2022)
Tetraphenyl porphyrin (TPP) has enormous potential for use as gas chromatography stationary phases because it has a distinctive extended π–π conjugated coplanar structure and a range of interesting properties such as a good solubility in dichloromethane, high melting point, and good thermal stability. In this work, a TPP column was successfully prepared using a static method. The column was nonpolar and had a high efficiency. The chromatographic selectivity of the TPP column was assessed. The TPP column showed superiority retention and higher resolution for alicyclic, aromatic molecules through ring matching and π-π stacking interaction comparable to HP-5MS column. The unique mechanisms through which the TPP column retained polychlorinated biphenyls allowed the peak pair of 2,2ʹ,5-trichlorobiphenyl and 4,4ʹ-dichlorobiphenyl to be resolved better on the TPP column than the HP-5MS column. The TPP column was thermally stable even at 260 °C for 2 h and gave results of a high degree of precision (run-to-run and column-to-column) with relative standard deviations <0.05% and <4.96%, respectively. The results indicated that porphyrin derivatives will be useful gas chromatography stationary phases.